PENINGKATAN LITERASI NUMERASI MELALUI POJOK BACA BAGI SISWA SEKOLAH DASAR UPTD SDI WAEWARU MELALUI PROGRAM KAMPUS MENGAJAR - Maria Goreti Kui; Ngurah Mahendra Dinatha; Afrianus Gelu (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The Kemendikbud School Literacy Movement Program defines literacy skills as the ability to access, understand, and use something intelligently through various activities, one of which is reading. The effort made is to create a reading habit in students. The government, through related agencies and various nongovernmental organizations, is trying to organize programs aimed at fostering a culture of reading, for example by setting up mobile libraries, reading gardens and reading corners. Just like schools in general, SDN 71 Maccini also has classrooms and displays that can make students comfortable during the learning process, but there is no special room in the classroom that will attract students to read. For this reason, a reading corner was held in each classroom to become a means for students to increase their reading interest.